One‐dimensional copper(II) coordination polymers based on 1, 3‐bis(pyridin‐4‐yl)propane and diimine ligands. Issue 5 (8th April 2019) - Bhat, Satish Shantaram; Shivalingegowda, Naveen; Revankar, Vidyanand Krishna; Kawade, Vitthal Ajinath; Butcher, Ray J.; Lokanath, Neratur Krishnappagowda
Abstract : Two one‐dimensional coordination polymers have been synthesized using [Cu(NO3 )(NN)(H2 O)]NO3, where NN is 2, 2′‐bipyridine or 1, 10‐phenanthroline, with 1, 3‐bis(pyridin‐4‐yl)propane as a linker, and have been structurally characterized. Abstract : Two one‐dimensional (1D) coordination polymers (CPs), namely catena ‐poly[[[aqua(2, 2′‐bipyridine‐κ 2 N, N ′)(nitrato‐κ O )copper(II)]‐μ‐1, 3‐bis(pyridin‐4‐yl)propane‐κ 2 N : N ′] nitrate], [Cu(NO3 )(C10 H8 N2 )(C13 H14 N2 )(H2 O)]·NO3 n (1 ), and catena ‐poly[[[aqua(nitrato‐κ O )(1, 10‐phenanthroline‐κ 2 N, N ′)copper(II)]‐μ‐1, 3‐bis(pyridin‐4‐yl)propane‐κ 2 N : N ′] nitrate], [Cu(NO3 )(C12 H8 N2 )(C13 H14 N2 )(H2 O)]·NO3 n (2 ), have been synthesized using [Cu(NO3 )(NN)(H2 O)2 ]NO3, where NN = 2, 2′‐bipyridine (bpy) or 1, 10‐phenanthroline (phen), as a linker in a 1:1 molar ratio. The CPs were characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis and single‐crystal X‐ray structure determination. The 1, 3‐bis(pyridin‐4‐yl)propane (dpp) ligand acts as a bridging ligand, leading to the formation of a 1D polymer. The octahedral coordination sphere around copper consists of two N atoms from bpy for1 or phen for2, two N atoms from dpp, one O atom from water and one O atom from a coordinated nitrate anion. Each structure contains two crystallographically independent chains in the asymmetric unit and the chains are linked via hydrogen bonds into a three‐dimensional network.